2022
DOI: 10.3389/fmicb.2022.865768
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Effects of Microplastics and Sulfadiazine on the Microalgae Chlamydomonas reinhardtii

Abstract: Despite the fact that microplastics (MPs) facilitate the adsorption of environmental organic pollutants and influence their toxicity for organisms, more study is needed on the combination of MPs and antibiotics pollutant effects. In this study, polystyrene MPs (1 and 5 μm) and sulfadiazine (SDZ) were examined separately and in combination on freshwater microalga, Chlamydomonas reinhardtii. The results suggest that both the MPs and SDZ alone and in combination inhibited the growth of microalgae with an increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…When faced with external stress, SOD is rapidly activated to mitigate the ROS as ROS accumulation. Low levels of ROS can regulate multiple physiological and biochemical reactions in cells; however, ROS is evidently toxic to organisms at high concentrations [34,46]. In this experiment, the SOD activity of microplastic-treated algal cells exhibited a pattern of initial increase followed by a subsequent decrease.…”
Section: Discussionmentioning
confidence: 69%
“…When faced with external stress, SOD is rapidly activated to mitigate the ROS as ROS accumulation. Low levels of ROS can regulate multiple physiological and biochemical reactions in cells; however, ROS is evidently toxic to organisms at high concentrations [34,46]. In this experiment, the SOD activity of microplastic-treated algal cells exhibited a pattern of initial increase followed by a subsequent decrease.…”
Section: Discussionmentioning
confidence: 69%
“…The dose-response analysis demonstrates a noticeable pattern in which higher concentrations of microplastics result in significant disruptions in photosynthetic efficiency (Tunali M et al, 2020), as indicated by the decreasing Fv/Fm ratios. This ratio is a crucial measure of the highest possible quantum efficiency of photosystem II (PSII), which is necessary for the light-dependent processes of photosynthesis (Li Z et al, 2022). A decrease in Fv/Fm indicates that microplastics may be causing physical harm to the photosynthetic equipment or triggering oxidative stress that hampers the functioning of PSII (Wu D, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…PE microplastics commonly arise from the decomposition of items such as plastic bags, bottles, and films through physical, chemical, and photo-degradation mechanisms (Govindan N et al, 2021). Microplastics possess notable attributes of flexibility and durability, enabling them to endure in the environment for prolonged durations (Li Z et al, 2022). Conversely, microplastics from consumer items such as foam packing, cups, and food containers are the usual source of PS microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Chlamydomonas has demonstrated high efficiency with the following compounds: Chlamydomonas sp. with 7-amino-cephalosporanic acid [84], C. mexicana with enrofloxacin [85], and C. reinhardtii with carbamazepine, ciprofloxacin, erythromycin, estrone, norfloxacin, ofloxacin, paracetamol, progesterone, roxithromycin, salicylic acid, sulfadiazine, sulfadimethoxine, sulfametoxydiazine, sulfamethazine, triclocarban, triclosan and trimethoprim [86], sulfadiazine [87] and ibuprofen [88]. C. reinhardtii has been found to biotransform antibiotics like azithromycin, erythromycin, and sulphapyridine [89].…”
Section: Chlamydomonas Phycoremediationmentioning
confidence: 99%